El profesor Theo van Boven fue distinguido por la Universidad de Buenos Aires como Doctor Honoris Causa - Revista Academia (2012)
At a ceremony held on November 26th in the Aula Magna of the Faculty of Law, Professor Monica Pinto delivered a laudatio on the occasion of being named Doctor Honoris Causa of the UBA.